Ordinance 3992/2017: challenges and advances for resource management in the Brazilian Unified Health System (SUS) - Pereira, Blenda Leite Saturnino; Oliveira Junior, Antonio Carlos Rosa de; Faleiros, Daniel Resende (Revista de Saúde Pública, 2019)
To advance in order to overcome the challenge of enabling greater autonomy in the use of financial resources in the Unified Health System (SUS), system managers agreed that transfers from the Union to other federated entities will be carried out through a financial investment account and a costing account. Over the past few years, states and municipalities managed more than 34,000 bank accounts dedicated to the Union’s on-lendings, in which balance exceeded R8 billion. However, from 2018, Ordinance 3,992/2017 unequivocally separated the budget flow from the financial flow, and the fund-to-fund transfers started to be carried out in only 11,190 bank accounts. Since then, managers have had financial autonomy in the management of financial resources received from the Union, if in accordance w